Astragalus improves intestinal barrier function and immunity by acting on intestinal microbiota to treat T2DM: a research review - Su, Min; Tang, Ting; Tang, Weiwei; Long, Yu; Wang, Lin; Liu, Meiling (Frontiers in Immunology, 2023)
Diabetes is a significant chronic endocrine/metabolism disorder that can result in a number of life-threatening consequences. According to research, the gut microbiota is strongly linked to the development of diabetes, making it a viable target for diabetes treatment. The intestinal microbiota affects intestinal barrier function, organism immunity, and thus glucose metabolism and lipid metabolism. According to research, a disruption in the intestinal microbiota causes a decrease in short-chain fatty acids (SCFAs), alters the metabolism of bile acids (BAs), branched-chain amino acids (BCAAs), lipopolysaccharide (LPS), and endotoxin secretion, resulting in insulin resistance, chronic inflammation, and the progression to type 2 diabetes mellitus (T2DM). Astragali Radix is a medicinal herb of the same genus as food that has been extensively researched for treating diabetes mellitus with promising results in recent years. Polysaccharides, saponins, flavonoids, and other components are important. Among them, Astragaloside has a role in protecting the cellular integrity of the pancreas and liver, can leading to alleviation of insulin resistance and reducing blood glucose and triglyceride (TC) levels; The primary impact of Astragalus polysaccharides (APS) on diabetes is a decrease in insulin resistance, encouragement of islet cell proliferation, and suppression of islet β cell death; Astragali Radix flavonoids are known to enhance immunity, anti-inflammatory, regulate glucose metabolism and control the progression of diabetes. This study summarizes recent studies on Astragali Radix and its group formulations in the treatment of type 2 diabetes mellitus by modulating the intestinal microbiota.